Faktor Risiko Persalinan Tanpa Pertolongan Tenaga Kesehatan di Kabupaten Banjarnegara Tahun 2018 - Abdullah Abdullah; Eugenius Phyowai Ganap (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
The risk factors of medically unassisted baby delivery in Banjarnegara DistrictPurpose: This study aims to identify risk factors of medically unassisted baby delivery in Banjarnegara Regency. Method: Mix method research design (case-control completed with in-depth interview). The sample size was 112 with a ratio of 1: 1 (56 cases and 56 controls), taken by simple random sampling based on secondary data PWS-KIA Banjarnegara District Health Office in 2018 including a qualitative sample of 5 people taken purposively. Data collection was carried out by means of interviews using questionnaires and interview guides. Analysis of bivariable data with McNemar test and multivariable with multiple logistic regression using the STATA 13.1 program. Results: Thirty-four (60.7%) respondents who gave birth without the help of health workers had a low educational level. The result of multivariable analysis showed a significant relationship between maternal education (aOR = 4.06; 95% CI = 1.32-12.45), history of ANC (aOR = 4.26; 95% CI = 1.24-14.64 ) and family support (aOR = 7.16; 95% CI = 1.73-29.51). Qualitative results show that prior delivery experience was the reason why women chose to give birth at home without the help of health workers. Conclusion: Childbirth without the help of health workers in Banjarnegara District was influenced by maternal education, ANC history, and family support. It is expected that families can be involved in providing Information and Education Communication (IEC) during ANC visits of pregnant women to increase awareness and knowledge related to safe pregnancy and childbirth.